Desmontando o “formigueiro humano”: uma leitura barthesiana das fotografias de Serra Pelada por Sebastião Salgado - Lavarda, Marcus Túlio Borowiski (2017)
This paper aims to analyze Sebastião Salgado’s photographs about the region of Serra Pelada and its gold-mining activities that took place mainly from 1980 to 1992. This study focuses mainly in a photo series called Ouro, Serra Pelada, Brasil (Gold, Serra Pelada, Brazil), which is part of Salgado’s masterpiece Workers (1996). This monumental body of photographic work depicts what was coined by the Brazilian media at that time “a human ant nest”. The methodology used in this study is an analysis of document-based bibliographical research on reference papers about Salgado’s work as well as other journalistic photos of the gold mine pits, such as the ones published in Brazilian journalist Ricardo Kotscho’s book Serra Pelada: uma ferida aberta na selva (1984). The main theoretical concept used was Roland Barthes’ semiology, particularly the Barthesian concept of myth – viewed as a system of signs that indefinitely expands the initial representations of the meaning. The theoretical framework of this paper also relies on reference studies on the Barthesian critique. The assumption of this study is that Salgado’s photographic work relies on the process of super construction of themes – as most photographers do – as described in Barthes’ Mythologies. This is thought to be a relevant theme for investigation because no scholars have scrutinized Salgado’s Serra Pelada yet – hence this attempt to analyze Salgado’s work from an academic perspective